Function of life meaning and marital communication among Iranian spouses in Universiti Putra Malaysia - Kalantarkousheh, Seyed Mohammad; Hassan, Siti Aishah (Elsevier, 2010)
Previous researches have demonstrated that meaning of life has an essential role in human's life. It is believed that meaning of life is an important issue in matrimony. However, there is a gap in literature to explain any relationship between meaning of life and marital communication. Purpose in Life Test (PIL), logo therapy, and Marital Communication of ENRICH were administered to fifty seven married spouses. The findings indicated the reliability of the employed instruments. In addition, the results highlighted a significant relationship between marital communication and meaning of life.